Determinants of native and non‐native plant community structure on an oceanic island. Issue 9 (7th September 2017) - Paudel, Shishir; Benavides, Juan C.; MacDonald, Beau; Longcore, Travis; Wilson, Gail W. T.; Loss, Scott R.
Abstract: Understanding the relative importance of environmental and anthropogenic factors in driving plant community structure, including relative dominance of native and non‐native species, helps predict community responses to biological invasions. To assess factors influencing plant communities on San Clemente Island, USA, we conducted an islandwide vegetation survey in which we measured plant species richness and percent cover of native and non‐native plants, as well as physical environmental variables, soil chemical properties, abundance of soil microbial functional groups (e.g., arbuscular mycorrhizal fungi [AMF]), and a human disturbance variable (distance to road). We found that total plant species richness decreased with increasing non‐native plant cover, soil pH, and AMF abundance. Native plant cover increased with increasing distance to a major paved road and decreased with increasing soil moisture and pH. Non‐native plant cover decreased with increasing distance to a major paved road and increased with increasing soil moisture, AMF abundance, and from southwest to northeast, a geographic/climatic gradient that represents increasing moisture. Nonmetric multidimensional scaling ordination further illustrated that trends in plant community composition were correlated with elevation, distance to a major paved road, and soil moisture, organic matter, and ammonium. These results suggest complex effects of physical environmental, soil chemical, and human‐related factors on plant community structure on an oceanic island, and moreover, that different factors affect cover of native and non‐native plants. Notably, our observation of apparent moisture limitation of non‐native plants suggests that, in some contexts, drought conditions can limit plant invasions and may even represent an opportunity for efficient control or eradication of invasive plants. The apparent negative effect of non‐native plants on native plant cover and overall plant species richness represents a conservation concern for native biodiversity on oceanic islands and suggests the potential for community reassembly as invasive species increasingly dominate due to anthropogenic disturbances.